Perceptions of deaf college students and graduates on their educational programs - Cabutihan, May Tabares (2005)
Post-secondary education plays a key role in determining the future of the deaf. This study sought the perceptions of deaf college students and graduates in five components of their educational program, namely faculty; non-academic staff; curriculum; physical fitness, equipment and assistive technology; and support services. A self-designed questionnaire and open ended questions were administered to the respondents using exact English and Filipino sign language. Deaf college students and graduates perceive the five factors except assistive technology, interpreters, and spiritual and counseling services favorably but have negative perception of notetakers in terms of attitude, competence, professionalism, and affordability and the job placement coordinator. They share similar perception on all components of the academic program.